The Implementasi Model PjBL-STEAM konteks lahan basah untuk meningkatkan kemampuan berpikir kritis dan self-efficacy peserta didik - Rusmansyah Rusmansyah; Siti Awalia Rahmah; Syahmani Syahmani; Abdul Hamid; Isnawati Isnawati; Arief Ertha Kusuma (University of Muhammadiyah Malang, 2023)
The PjBL-STEAM model of wetland contexts is a learning model that can improve students' critical thinking and self-efficacy skills. It is carried out by utilizing the wetland environment as a medium for learning electrolyte and nonelectrolyte solutions. This study aims to determine the improvement of students’ critical thinking and self-efficacy through the PjBL-STEAM model in the context of wetlands. This present study employed quasi-experimental experiment with a one-group pretest-posttest research design. The participants were obtained through convenient sampling with the inclusive criteria of students of class X MIA 3 at SMAN 3 Barabai. The data were obtained through critical thinking tests and self-efficacy questionnaires. The obtained data were analyzed through descriptive analysis. The results showed that the PjBL-STEAM model in the wetland context could improve the critical thinking ability and self-efficacy of students with an N-gain value of critical thinking ability of 0.58, with a moderate category and N-gain self-efficacy of 0.75 with a high category. In other words, applying the PjBL-STEAM model in wetland contexts effectively improves students' critical thinking and self-efficacy skills.